A ratiometric fluorescent probe for the detection of β-galactosidase and its application. Issue 22 (9th April 2021) - Li, Yanan; Deng, Bing; Chen, Haitao; Yang, Shaoxiang; Sun, Baoguo
Abstract : A ratiometric fluorescent probe was successfully used as a tool to determine β-galactosidase activity in fruits. Abstract : Herein, a coumarin fluorescent probe (Probe 1 ) was developed for the ratiometric detection of β-galactosidase (β-gal) activity. The detection range was 0–0.1 U mL −1 and 0.2–0.8 U mL −1, and the limit of detection (LOD) was 0.0054 U mL −1 . Moreover, the luminous intensity of Probe 1 increased gradually with increase in β-gal activity. It could be observed under 254 nm UV irradiation by the naked eye. Furthermore, this method only required a small amount of sample (20 μL) and a short analytical time (30 min) for the detection of β-gal activity with a low LOD. Probe 1 was successfully used to detect β-gal activity in real fruit samples, and can be applied to the quantitative and qualitative detection of β-gal activity.